Kota Rempah: Strengthening Ternate’s Brand Identity through Gastronomic Souvenirs for a Sustainable Tourism - Yulius, Kevin Gustian; Yuliantoro, Nonot; Timba, Yosep Dudedes (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2025)
Ternate is celebrated for its historic spice trade and has recently adopted the Kota Rempah brand to promote its culinary heritage in support of sustainable tourism. This study examines 93 local MSMEs and their 48 unique gastronomic souvenirs—from nutmeg and kenari confections to seafood preserves—to evaluate their contributions to place identity and inclusive economic growth. Utilizing a qualitative case study design, data were gathered through semi-structured interviews with tourism office and Dekranasda officials, MSME owners, and field observations. Findings reveal that most enterprises cluster in urban districts, a diverse product range rooted in local ingredients, and strong stakeholder interest tempered by challenges in branding consistency, packaging, and geographic reach. The analysis highlights how culinary souvenirs function as cultural carriers, fostering emotional connections, longer visitor stays, and repeat visitation, while also empowering women led businesses and community livelihoods. To harness these opportunities, integrated policy measures are recommended, including shared packaging facilities, cohesive Kota Rempah branding guidelines, and expanded support for peripheral areas. Finally, pursuing geographic indication status for key spice products is proposed to protect authenticity, enhance market differentiation, and further advance sustainable tourism development in Ternate.